Aktivitas antioksidan dan uji sitotoksik infusa daun jarak pagar (Jatropha curcas) - Sudarman Rahman; Alayya Adistia Putri; Erwin Prasetya Toepak; Stevin Carolius Angga; Ysrafil Ysrafil (Universitas Mataram, 2023)
Antioxidants are crucial in preventing cell damage caused by oxidation from oxidants. The use of antioxidants from natural products such as Jatropha curcas leaves can counteract free radicals due to the presence of secondary metabolites. The main aims of the study were to determine the antioxidant and cytotoxic activity of the infusion of J. curcas leaves. The sample was extracted using the infusion method. A qualitative phytochemical screening was carried out using the test tube method, antioxidant assay using the DPPH method and cytotoxic using the BSLT method. The results showed that the infuse of J. curcas leaves contained secondary metabolites such as polyphenols and tannins, alkaloids, flavonoids, and saponins. In the antioxidant activity test, infuse of J. curcas leaves and vitamin C (control) the IC50 was 58.90±2.34 ppm and 8.78±0.21 ppm respectively. The infused cytotoxic test contained an active toxic compound in shrimp larvae with an LC50 of 200.28 ppm (LC50 ≤ 1000 ppm). Based on the results of the study, infuse of J. curcas leaves showed potential as an antioxidant and anticancer agent with a strong classification.